2021
DOI: 10.1021/acsnano.1c05321
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Melanosomes Promote Orientation-Selective Delivery and Melanocyte Pigmentation in the H2O2-Induced Vitiligo Mouse Model

Abstract: Extremely limited drug retention and depigmentation represent the greatest barriers against vitiligo treatment advancement. Here, inspired by biological melanosomes, the primary melanin transporter, we developed biomimetic melanosomes to combat reactive oxygen species (ROS)-mediated melanocyte damage and depigmentation. Briefly, methylprednisolone (MPS) and melanin-mimicking polydopamine (PDA) were encapsulated inside lysine–proline–valine (KPV)-modified deformable liposomes (KPV-Lipos). Owing to their phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Tyrosinase is a key enzyme in melanin production that catalyzes the conversion of l -tyrosine to l -DOPA and then to dopachrome, which subsequently spontaneously polymerizes to melanin through a series of reactions. Thus, we measured tyrosinase activity by monitoring the oxidation of 3,4-dihydroxyphenylalanine (dopa) into the red-colored dopachrome, , which revealed that tyrosinase activity increased in the presence of 1 in a concentration-dependent manner, reaching a maximum (146.1 ± 8.396%) in 100 μM treatments (Figure d and Figure S9a). Determination of melanin content by fluorescence spectroscopy further showed that melanin production was enhanced with increasing concentrations of 1 ( Figure e), reaching 209.5 ± 22.51% after the treatment with 100 μM 1 , compared to 170 ± 7.252% in the NDP-α-MSH group relative to untreated controls (Figure S9b).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosinase is a key enzyme in melanin production that catalyzes the conversion of l -tyrosine to l -DOPA and then to dopachrome, which subsequently spontaneously polymerizes to melanin through a series of reactions. Thus, we measured tyrosinase activity by monitoring the oxidation of 3,4-dihydroxyphenylalanine (dopa) into the red-colored dopachrome, , which revealed that tyrosinase activity increased in the presence of 1 in a concentration-dependent manner, reaching a maximum (146.1 ± 8.396%) in 100 μM treatments (Figure d and Figure S9a). Determination of melanin content by fluorescence spectroscopy further showed that melanin production was enhanced with increasing concentrations of 1 ( Figure e), reaching 209.5 ± 22.51% after the treatment with 100 μM 1 , compared to 170 ± 7.252% in the NDP-α-MSH group relative to untreated controls (Figure S9b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…3 However, the therapeutic outcomes are unsatisfactory, with a wide range of side effects, and thus no drugs have received FDA approval for vitiligo. 4 Melanocortin 1 receptor (MC1R) is a G-protein coupled receptor present on the surface of melanocytes. Upon ultraviolet (UV) irradiation, MC1R is bound by keratinocyte-derived αmelanocyte-stimulating hormone (α-MSH) to activate cAMP signaling, subsequently enhancing melanin production, and therefore presenting a possible therapeutic target for vitiligo.…”
mentioning
confidence: 99%
“…The current study further showed that FA was able to protect melanocytes from oxidative injury by lowering intracellular ROS levels and upregulating HO-1 and SOD2, both of which were reported deficient in vitiligo melanocytes [ 3 , 5 ]. Further studies using H 2 O 2 -induced vitiligo animal model [ 22 ] are needed to confirm the protective effect of FA on melanocytes from H 2 O 2 -triggered oxidation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…One research study applied a 5% H 2 O 2 solution at a depilated area of about 40 cm 2 on the dorsal skin of black guinea pigs, 0.5 ml each time, twice a day for 50 days [9]. During that time, the black skin of the guinea pigs turned white and even grew white hair.…”
Section: Hydrogen Peroxide (H 2 O 2 )mentioning
confidence: 99%